PENERAPAN METODE STUDENT TEAMS ACHIEVEMENT DIVISION SEBAGAI UPAYA MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN SISTEM PENGAPIAN - Novi Griya Legita; Suparmin Suparmin (Universitas Sarjanawiyata Tamansiswa, 2013)
The purpose of this study was to describe the learning process to improve student achievement SMK XI TKR Tamtama Kroya on subjects ignition system through the implementation of cooperative learning method Student Teams Achievement Division. The subjects of this research was student of class XI TKR 4 SMK Tamtama Kroya totaling 28 student. The objects of this research was learning activities and ignition system learning achievement. This was indicated by an increase in the result percentage average learning activities score of 35,1 % in the pre-action, whereas at the first cycle improves with average percentage 48,5%. In the second cycle improve to 66,35%. ignition system learning achievement of student also increased. At the beginning of the test the ability is60,36.in the first cycle the average result improves to 60,69%. In the second cycle the average result improves to 70,23.